Emergency Regimes in the European Constitutions – A Comparative Overview - Attila Horváth (European Journal of Risk Regulation)
European constitutions differ greatly in the depth to which they deal with emergencies: while many constitutions devote more or less detailed regulation to emergency regimes, others almost completely neglect these issues or dedicate only some very short and vague references to emergency situations and powers. This article aims to carry out a systematic comparison of the emergency-related provisions of forty European constitutions, focusing on (1) the level of detail of the regulation, (2) the emergency regimes addressed, and (3) the restrictions on fundamental rights. As the study points out, only two out of the forty constitutions are completely silent on emergency powers. However, the remaining thirty-eight constitutions show wide variation in the level of detail of the emergency regulation; the vast majority of the emergency regimes are related to war or armed attack (or the danger thereof), to internal crises threatening the constitutional order, and to natural disasters. Concerning fundamental rights, the examination of the constitutional texts confirms that twenty-five out of the forty constitutions encompass some provisions on the restriction of these rights in a state of emergency.